IMA Genome-F 11 - Brenda D. Wingfield; Arista Fourie; Melissa C. Simpson; Vuyiswa S. Bushula-Njah; Janneke Aylward; Irene Barnes; Martin P. A. Coetzee; Léanne L. Dreyer; Tuan A. Duong; David M. Geiser; Francois Roets; E. T. Steenkamp; et al. (IMA Fungus, 2019)
Abstract Draft genomes of the fungal species Fusarium xylarioides, Teratosphaeria gauchensis and T. zuluensis are presented. In addition an annotation of the genome of Ceratocystis fimbriata is presented. Overall these genomes provide a valuable resource for understanding the molecular processes underlying pathogenicity and potential management strategies of these economically important fungi.